Swimming goggle wear is not associated with an increased prevalence of glaucoma. Issue 2 (9th September 2014) - Franchina, Maria; Yazar, Seyhan; Booth, Lisa; Wan, Sue Ling; Cox, Kay; Kang, Min H; Hewitt, Alex W; Mackey, David A
Abstract : Background/aims: Previous studies have demonstrated a small but significant transient increase in intraocular pressure (IOP) in individuals wearing certain types of swimming goggles. These findings suggested that wearing goggles could represent a significant risk factor for developing and/or worsening of glaucoma in people who swim regularly. The aim of this study was to determine if glaucoma prevalence is increased among adult swimmers. Methods: A comprehensive ocular examination was performed on 231 members of local swimming clubs and 118 non-swimmers. IOP was measured using iCARE tonometry and visual field testing was performed using Humphrey SITA fast 24–2. Retinal nerve fibre layer thickness was assessed using spectral domain optical coherence tomography. Results: Based on measurements of IOP and visual fields, we did not detect any new cases of glaucoma in our cohort of frequent swimmers. Similarly, we found no difference in the thickness of the retinal nerve fibre layer between swimmers and non-swimmers; the mean right global thickness (GT) was 94.0 μm (IQR 88.0, 100.3) vs 93.0 μm (IQR 89.0, 101.0), respectively (p=0.976), and the median left GT was 93.7 μm (IQR 88.0, 101) in both groups (p=0.799). Conclusions: These findings suggest that frequently wearing swim goggles does not lead to an increased risk of glaucoma over time in adults.